African nature in reportages by Ryszard Kapuściński: literariness, faithfulness to facts, an individual vision of the world (based on the book Heban [the English title: The Shadow of the Sun]) - Kuryłowicz, Beata (Papers in Linguistics, 2020)
This article is an attempt to demonstrate the influence of literariness and faithfulness to facts on the way of expressing and forming an individual vision of the world in the literary reportage. On the one hand, the fact of showing reality in a documentary text is determined by the factual nature of the account. Hence, the author strives to present the truth about the world – the truth which is not so much an objective record of facts, but is rather marked by a subjective, personal perspective at events. On the other hand, the literary form (style) determines such a choice of devices and techniques of artistic expression that impose an individualized view of reality. Excerpts of Kapuściński’s reportages from the book Heban were used as an illustration of the theoretical considerations. The analysis presented in the article shows that the literary devices used (such as contrast, enumeration, vivid comparisons and metaphors) determined by the features of the genre (literary reportage) serve to convey the truth about the places described and help to accurately depict the essence of events or reveal various aspects of the described phenomena.